CONTRARREFORMA TRABALHISTA E PREVIDENCIÁRIA: implicações para os trabalhadores - Maria Lucia Lopes da Silva (Universidade Federal do Maranhão, 2017)
is article deals with the labor counter-reform ( PLC 38/2017) and social se- curity counter-reformation movement happening since 1998, under pressure from nancial capital, prioritizing its present moment under the Constitu tional Amendment Proposal (PEC) number 287, proposals for changes in the INSS functioning and management model expressed by the INSS Digital and Te - lework projects in INSS, in addition to the proposal to unify the SERPRO and DATAPREV databases, as well as their implications for employees.